Phlebectasis of the external jugular vein. - Lopes, C (1990)
Phlebactasia of the external jugular vein is a rare nosological entity. Few reports appeared in the world literature. Clinically it presents as a cervical mass enlarging with a Valsalva maneuver. The Authors present one clinical case, emphasizing the possibilities of Computed Tomography (CT) in a precise diagnosis, etiological and topographical, without using other invasive modalities.